(untitled) (Journal of Economic Research & Business Administration, 2017)
To enhance competition in the construction industry market productive activities of employees of the organization allows us to consider as a key factor as a strategic resource in achieving success. Currently, due to the efficient use of scarce resources, employees are often made with economic efficiency, through the use of that represents through the implementation of the organization’s goals and care workers, preferences, interests and needs for razrabotkoj characterizing “efficiency” is used more and more often. Proper placement of the workforce to jobs in the organization in accordance with the particular optimal assignment is the main purpose in planning taken by employees as polimernoe use of human resources. In some projects, the number of employees is governed by the adoption or dismissal of employees, Because, along with the adoption of the workforce and their dismissal is connected with additional costs.